Impact of Genetic Testing for Cardiomyopathy on Emotional Well-Being and Family Dynamics: A Study of Parents and Adolescents. (13th July 2021) - Ahimaz, Priyanka; Sabatello, Maya; Qian, Min; Wang, Aijin; Miller, Erin M.; Parrott, Ashley; Lal, Ashwin K.; Chatfield, Kathryn C.; Rossano, Joseph W.; Ware, Stephanie M.; Parent, John J.; Kantor, Paul; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Genetic testing is indicated for children with a personal or family history of hereditary cardiomyopathy to determine appropriate management and inform risk stratification for family members. The implications of a positive genetic result for children can potentially impact emotional well-being. Given the nuances of cardiomyopathy genetic testing for minors, this study aimed to understand how parents involve their children in the testing process and investigate the impact of genetic results on family dynamics. Methods: A survey was distributed to participants recruited from the Children's Cardiomyopathy Foundation and 7 North American sites in the Pediatric Cardiomyopathy Registry. The survey explored adolescent and parent participants' emotions upon receiving their/their child's genetic results, parent-child result communication and its impact on family functionality, using the McMaster Family Assessment Device. Results: One hundred sixty-two parents of minors and 48 adolescents who were offered genetic testing for a personal or family history of cardiomyopathy completed the survey. Parents whose child had cardiomyopathy were more likely to disclose positive diagnostic genetic results to their child ( P =0.014). Parents with unaffected children and positive predictive testing results were more likely to experience negative emotions about the result ( P ≤0.001) but also had better family functioning scores than those with negative predictive results ( P =0.019). Most adolescents preferred results communicated directly to the child, but parents were divided about whether their child's result should first be released to them or their child. Conclusions: These findings have important considerations for how providers structure genetic services for adolescents and facilitate discussion between parents and their children about results.